Immunochemical Localization of Parathyroid Hormone in Cancer Tissue from Patients with Ectopic Hyperparathyroidism - Genaro M. A. Palmieri; Robert E. Nordquist; Gilbert S. Omenn (The Journal of Clinical Investigation, 1974)
Immunoreactive parathyroid hormone (PTH) in nonparathyroid malignant tumors associated with hypercalcemia and hypophosphatemia in the absence of demonstrable bone metastases was determined by radioimmunoassay and immunofluorescent techniques. Six of seven tumors contained material with immunological cross-reactivity to bovine PTH by radioimmunoassay and immunofluorescence. The intensity of the immunofluorescent stain varied considerably in the different tumors. From 15 to 90% of neoplastic cells were stained specifically with fluorescein-labeled anti-PTH. In contrast, normal parathyroid glands and parathyroid adenomas showed uniform distribution of immunofluorescence in all parenchymal cells. In one malignant tumor, PTH was localized also by immunoautoradiography. In every case PTH was detected only in the cytoplasm of parenchymal cells. One patient lacked detectable PTH in his tumor, yet showed regression of the hypercalcemia to normal values after removal of large masses of neoplastic tissue and recurrence of hypercalcemia when new growth occurred. Dilutional radioimmunoassay curves of nonparathyroid malignant tumors were in most cases different from those obtained with extracts of normal parathyroid glands and parathyroid adenomas. Although both nonparathyroid neoplasmas and parathyroid extracts demonstrated immunoheterogeneity by gel filtration, greater heterogeneity was found in nonparathyroid malignant tumors. In those tumors in which immunological cross-reactivity to PTH was detected, the capability of secreting PTH may be restricted to derepressed cell clones amidst other neoplastic cells, whereas the greater heterogeneity of ectopic PTH may reflect hormone cleavage by proteolytic enzymes in the tumor that is less specific than the Pro-PTH cleaving enzyme in the parathyroids. Images